The ipsilateral human motor cortex can functionally compensate for acute contralateral motor cortex dysfunction. - Strens, L; Fogelson, N; Shanahan, P; Rothwell, J; Brown, P (2003)
What promotes motor recovery from stroke? To date, studies of recovery from stroke have shown alterations in function in various cortical areas, including the contralesional (unaffected) motor cortex (M1). However, whether these changes contribute to recovery or are mere epiphenomena remains unclear. We therefore sought evidence that the ipsilateral M1 can compensate for dysfunction of the contralateral M1. We recorded the change in force production during a finger-tapping task in response to acute disruption of M1 function by repetitive transcranial magnetic stimulation (rTMS). Neither control (occipital) nor ipsilateral M1 rTMS lead to a change in tapping force. RTMS over contralateral M1 had a short-lived effect and induced changes in ipsilateral M1 excitability around the time that these behavioral effects abated, consistent with delayed compensation by the ipsilateral M1. Simultaneous bilateral M1 stimulation, designed to prevent compensation by the ipsilateral M1, had a large and prolonged effect on tapping force. This is the first demonstration that the ipsilateral primary motor cortex is capable of functionally significant compensation for focal contralateral cortical dysfunction in the adult human and provides a rational basis for interventional treatments aimed at promoting functional compensation in unaffected cortical areas after stroke.